Genetic Diversity and Selection Signatures in Synthetic-Derived Wheats and Modern Spring Wheat - Ali, Mohsin; Danting, Shan; Wang, Jiankang; Sadiq, Hafsa; Rasheed, Awais; He, Zhonghu; Li, Huihui (Frontiers in Plant Science, 2022)
Common wheat is one of the widely grown cereal crops in the world. Synthetic hexaploid wheats and their relatives were subject to empirical selection in developing genetically superior cultivars. To investigate genetic diversity, patterns of nucleotide diversity, population structure and selection signatures during wheat breeding, we tested 422 wheat accessions, including 145 synthetic-derived wheats, 128 spring wheat cultivars, and 149 advanced breeding lines from Pakistan. A total of 18,589 high-quality GBS-SNPs were identified that were distributed across the A (40%), B (49%) and D (11%) genomes. Values of population diversity parameters were estimated across chromosomes and genomes. Genome-wide average values of genetic diversity (~0.30) and polymorphic information content (~0.25) were estimated, reflecting the presence of high genetic diversity in the studied panel. NJ-tree, PCA and kinship analyses revealed that synthetic-derived wheats and advanced breeding lines were genetically diverse. The 422 accessions were not separated into distinct groups by neighbour-joining analysis and confirmed using principal component analysis. This conclusion was validated with both relative kinship and Rogers genetic distance analyses. EigenGWAS analysis revealed that 32 unique genome regions had undergone selection. We found that 50% of the selected regions were located in the B-genome, 29% for D-genome and 21% for A-genome. Previously known functional genes or QTL were found within selection regions associated with phenology-related traits such as vernalization, adaptability, disease resistance and yield-related traits. The selection signatures identified in the present investigation will be useful for understanding targets of modern wheat breeding in Pakistan.